Synthesis of novel naphthoquinone-spermidine conjugates and their effects on DNA-topoisomerases I and II-alpha - Cunha Andréa S.; Lima Edson L. S.; Pinto Angelo C.; Esteves-Souza Andressa; Echevarria Aurea; Camara Celso A.; Vargas Maria D.; Torres José C. (Journal of the Brazilian Chemical Society, 2006)
Novel derivatives of lapachol 2, nor-lapachol 3 and lawsone 4 have been synthesized by nucleophilic displacement of the methoxynaphthoquinones 2a, 3a and 4a with the polyamine (PA) N¹-Boc-N5-Bn-spermidine 1a. The respective products 2b-4b were obtained in good yields and characterized by spectroscopic and analytical methods. The inhibitory action of these naphthoquinone-PA conjugates on DNA-topoisomerases (topo) I and II-alpha was evaluated by relaxation assay of supercoiled DNA plasmid. All compounds (1a 2b, 3b and 4b) presented significant inhibition of topo II-alpha catalytic activity at the 2 µM dose. Considering that only PA 1a did not inhibit the enzyme catalytic activity at the 0.2 µM dose, the appended naphthoquinone moiety acts as a "value added" fragment. Compounds 1a 2b, 3b and 4b did not inhibit the enzyme DNA-topo I at the 200 µM dose.